2018
DOI: 10.1177/1747021817739221
|View full text |Cite
|
Sign up to set email alerts
|

Gaze in a real-world social interaction: A dual eye-tracking study

Abstract: People communicate using verbal and non-verbal cues, including gaze cues. Gaze allocation can be influenced by social factors; however, most research on gaze cueing has not considered these factors. The presence of social roles was manipulated in a natural, everyday collaborative task while eye movements were measured. In pairs, participants worked together to make a cake. Half of the pairs were given roles ("Chef" or "Gatherer") and the other half were not. Across all participants we found, contrary to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 31 publications
1
51
0
1
Order By: Relevance
“…The field of social attention, as briefly discussed previously, is primarily focused on how attention is influenced by socially relevant objects, events, and situations, most notably, interactions with other social agents. In recent decades, it has been argued extensively that the experimental arrangements used by researchers in this field need more 'ecological validity' in order to adequately study the relevant characteristics of social attention in the 'realworld' (Risko et al, 2012(Risko et al, , 2016Schilbach et al, 2013;Caruana et al, 2017;Macdonald and Tatler, 2018;Shamay-Tsoory and Mendelsohn, 2019). In the light of these concerns, several researchers have advocated to study "real-world social attention" (Risko et al, 2016, p. 1) and "real-world social interaction" (Macdonald and Tatler, 2018, p. 1; see also Shamay-Tsoory and Mendelsohn, 2019).…”
Section: The Field Of Social Attention: Away From the Real-world And mentioning
confidence: 99%
See 1 more Smart Citation
“…The field of social attention, as briefly discussed previously, is primarily focused on how attention is influenced by socially relevant objects, events, and situations, most notably, interactions with other social agents. In recent decades, it has been argued extensively that the experimental arrangements used by researchers in this field need more 'ecological validity' in order to adequately study the relevant characteristics of social attention in the 'realworld' (Risko et al, 2012(Risko et al, , 2016Schilbach et al, 2013;Caruana et al, 2017;Macdonald and Tatler, 2018;Shamay-Tsoory and Mendelsohn, 2019). In the light of these concerns, several researchers have advocated to study "real-world social attention" (Risko et al, 2016, p. 1) and "real-world social interaction" (Macdonald and Tatler, 2018, p. 1; see also Shamay-Tsoory and Mendelsohn, 2019).…”
Section: The Field Of Social Attention: Away From the Real-world And mentioning
confidence: 99%
“…In the light of these concerns, several researchers have advocated to study "real-world social attention" (Risko et al, 2016, p. 1) and "real-world social interaction" (Macdonald and Tatler, 2018, p. 1; see also Shamay-Tsoory and Mendelsohn, 2019). One example of this is given by Macdonald and Tatler (2018). In this study, Macdonald and Tatler (2018) investigated how social roles given to participants influenced their social gaze behavior during a collaborative task: baking a cake together.…”
Section: The Field Of Social Attention: Away From the Real-world And mentioning
confidence: 99%
“…Such changes in cognition and behavior are sometimes referred to as 'social presence' or 'mere presence' effects [28][29][30][31]. Similarly, other eye-tracking studies have further demonstrated that gaze behavior can be modulated by social presence and potential interactions [9,12,32,33]. However, it is not always clear under what circumstances social presence may cause changes in people's gaze behavior, or how gaze behavior may be modulated as a result.…”
Section: Gaze Behavior In Context: Social Presence and Potential Intementioning
confidence: 99%
“…Compared to tower-mounted and remote eye trackers, which typically constrain participants to a chair and possibly a chin rest, head-worn eye trackers allow recording eye movements from participants that freely move around. This enables many studies that are not feasible with screenbased eye trackers, such as decision-making research in supermarkets (Gidlöf, Wallin, Dewhurst, & Holmqvist, 2013;Gidlöf, Anikin, Lingonblad, & Wallin, 2017), viewing behavior of medical professionals (Dik, Hooge, van Oijen, & Siersema, 2016), shared manipulation in human-robot interaction (Aronson et al, 2018), foot placement in difficult terrain (Matthis, Yates, & Hayhoe, 2018), visual behavior of teachers in a classroom (McIntyre, Jarodzka, & Klassen, 2017;McIntyre & Foulsham, 2018), as well as dyadic interaction between adults (Ho, Foulsham, & Kingstone, 2015;Rogers, Speelman, Guidetti, & Longmuir, 2018;Macdonald & Tatler 2018; although some interaction studies have been performed with remote eye trackers, see Hessels, Cornelissen, Hooge, & Kemner, 2017;Hessels, Holleman, Kingstone, Hooge, & Kemner, 2019) or children and their parents (Yu & Smith 2017;Suarez-Rivera, Smith, & Yu, 2019).…”
Section: Introductionmentioning
confidence: 99%